Smuggling Activities and its Effects on Religious Institutions in Border Areas of Ogun State, Nigeria - Obasola, Kehinde Emmanuel; Akinniyi, Samson Abayomi (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
It is instructive to note that the issue of smuggling calls for concern. This is due to the havoc that is perpetrated not only to the socio-economic climate of the nation, but also to the religious uneasiness that results from the activities of smugglers in Idiroko and its environs in Ogun State. The social impact of the activities of this group calls for speedy intervention by both the government and the religious organisations. Lives have been indiscriminately lost in the process of the operation of this group. Economic activities are paralysed and religious activities hindered. It is in this view that this paper examines a socio-religious assessment with the view to knowing the impact it has on religious institutions within the area of study. The study posits that the activities of smugglers are inimical not only to the economic growth of the nation but also to the spiritual dimension of the people by inhibiting the process of fellowship and religious activities which occur on worship days. As such, efforts should be made by both the government and religious leaders to mitigate their activities. Keywords: Smuggling Activities, Religious Institutions, Christianity, Islam, Ogun State